2018
DOI: 10.4172/2155-9546.1000531
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of three Imported Fresh Locally Produced Marine Fishes in Al-Faw City, Basrah, Iraq

Abstract: The present study was conducted to determine microbial quality have been measured in gills and gut tissues in three imported fishes samples obtained from trawl fishing boats in Al-Faw city, Basrah, Iraq. In this study, tissues samples were collected from 80 fish samples of three fresh marine fish species: silver pomfret Pampus argenteus (Euphrasen, 1788); Oriental Sole Brachirus orientalis (Bloch & Schneider, 1801) and Yellowfin seabream, Acanthopagrus latus (Houttuyn,. 1782) were collected from trawl fishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The densities of TCs and FCs in this study are in agreement with Donde et al (2014), who observed that the density of TCs in the skin and gills was higher that of than FCs in fish from Naivasha Lake, Kenya. The prevalence of coliform bacteria in fish could be linked to contamination from the surrounding water environment (Al‐Sheraa, 2018; Kluga, Kacaniová, Kantor, Kovalenko, & Terentjeva, 2017), and the presence in the gills could be attributed to the high specific surface area for bacterial attachment and high water flow passing through them, including organic substances (Kluga et al, 2017). In the present study, the highest TC and FC densities from the skin were recorded in the spring and winter, respectively, while the highest TC and FC densities for the gills were observed in the summer and winter, respectively (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The densities of TCs and FCs in this study are in agreement with Donde et al (2014), who observed that the density of TCs in the skin and gills was higher that of than FCs in fish from Naivasha Lake, Kenya. The prevalence of coliform bacteria in fish could be linked to contamination from the surrounding water environment (Al‐Sheraa, 2018; Kluga, Kacaniová, Kantor, Kovalenko, & Terentjeva, 2017), and the presence in the gills could be attributed to the high specific surface area for bacterial attachment and high water flow passing through them, including organic substances (Kluga et al, 2017). In the present study, the highest TC and FC densities from the skin were recorded in the spring and winter, respectively, while the highest TC and FC densities for the gills were observed in the summer and winter, respectively (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Quality and safety of the fish products and particularly frozen food is one of the main problems of food industry today. The presence or absence of food borne pathogens (particularly staphylococcus aureus and Escherichia coli) in a fish product is a function of harvest environment and sanitary conditions during capture, processing, distribution and/or storage (Hala et al, 2017;Al-Sheraa, 2018). This suggests that fishes can be contaminated by both aquatic environment and post-harvesting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high nutritive value, sea fishes are a major vehicle for pathogenic bacteria. Fishes can be contaminated by both aquatic environment and postharvesting condition (Al-Sheraa, 2018). Due to the attack of pathogenic bacteria and fungi a wide ranges of sea fishes spoilages occurs which adversely affect the economic condition in Bangladesh and as well as public health.…”
Section: Introductionmentioning
confidence: 99%